Examining Consumer Purchase Intentions in Agricultural Live Streaming Using an Extended Model of Goal-Directed Behavior - Xiaolu Han (SAGE Open)
Live streaming for assisting farmers (LSAF) is a form of cause-related marketing. Consumers’ purchase intentions during live streaming is related not only to the content of the live streaming but also to consumers’ motivation, cognition, and anticipated emotions. This study integrates the influence of individual self-construal on behavioral attitudes into the theory of goal-directed behavior from the perspective of consumer psychology and constructs a structural equation model of the factors influencing consumer purchase intentions in LSAF. A survey and interviews involving 232 consumers were carried out, and the model was empirically tested using SPSS and AMOS software. The results highlight the diverse impacts of consumer self-construal on attitudes toward such live streaming events, with attitudes, subjective norms, and positive anticipated emotions positively influencing the desire to purchase, whereas negative anticipated emotions negatively influencing this desire The desire to purchase as well as perceived behavioral control positively influence consumers’ purchase intentions. Using the EMGB framework, this study contributes to a deeper understanding of the complex mechanisms involved in shaping the purchase intention in cause-related marketing. The findings offer valuable insights for live streaming e-commerce companies looking to target and optimize LSAF, as well as to enhance consumers’ purchase intentions.